Recycling of Carbon Fiber/Poly (Ether Ether Ketone) Composite's Milling Dust/Chips - Altinbay, Aylin; Dogu, Mustafa (WILEY, 2026)
Significant amounts of milling dust and chips (D/C) are obtained during the machining of composite materials. In this study, D/C generated during the machining of carbon fiber reinforced poly(ether ether ketone) (CF/PEEK) composites was utilized to produce discontinuous CF/PEEK through compression molding. However, it was observed that D/C was generated at various sizes and with considerable deformations during the machining process. Also, it was noticed that the cutting fluid used in the machining process contains oil. These problems could harden the compression molding process and decrease mechanical properties. To address these issues, the D/C was first washed before proceeding with compression molding. Additionally, polyetherimide (PEI) was employed as a compatibilizer at various concentrations to improve mechanical results. The moldability of D/C and the effect of PEI incorporation on the properties of the resulting composites were assessed through thermal and mechanical characterizations. It was deduced that cleaning the D/C prior to processing significantly improved the mechanical properties. Moreover, incorporating PEI further enhanced these properties, with optimal results observed at a concentration of 1 wt.% PEI.
Keywords: mechanical performance; milling dust/chips; PEEK composite; PEI; recycling; PERFORMANCE THERMOPLASTIC COMPOSITES; MECHANICAL-PROPERTIES; CRYSTALLIZATION BEHAVIOR; PEEK; INTERFACE; Materials Science; Polymer Science